SUSTAINABILITY CONCEPT OF BALI AGA ARCHITECTURE - Ni Ketut Ayu Siwalatri (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2013)
Architecture is one of human works that consumed a lot of energy. Present research shows that architecture consumed more than 50% of total energy in the world. That is why awareness of sustainability issues become prominent issues among architects, architecture students and academics. Practically sustainability concept is not some thing new for some countries. Traditional settlements used similar concept to sustainability concept, for example Bali Aga settlement. The settlement showed how the community used the concept as tradition and way of their life.The Bali Aga architecture was developed between 9 to-11 AD and mostly located in the highland or the mountain of Bali. The word “Aga” is used to distinguish the highland settlements from the rest of traditional settlements of Bali which mainly located in the down line of Bali, particularly in the southern Bali. Bali Aga settlements are located mostly in eastern and northern Bali. The village of Tenganan is the prime example of the genre, and for this discourse, the research site was Julah village in Buleleng Regency. This village is located on the northern part of Bali.Referring to Bali Aga’s traditions and customs, the community recognized the relationship between the people and the environment. Bali Aga architecture shows the expression of their tradition that keep the environment sustained. This paper will discuss about tradition of Bali Aga community and how they articulated through their architecture. The aims of this study are to increase the awareness of modern soceity on sustainability issues and learned from tradition of Bali Aga community how to keep environment friendly.